Non-aqueous electrolyte secondary battery
Patent Information
- Application Number
- JP2021550377
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-09-30
- Filing Date
- 2020-07-28
- Publication Date
- 2025-02-17
- Estimated Expiration
- 2040-07-28
Smart Images

Figure 0007630082000002 
Figure 0007630082000003 
Figure 0007630082000001
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a non-aqueous electrolyte secondary battery. [Background technology]
[0002] In recent years, non-aqueous electrolyte secondary batteries that include a positive electrode, a negative electrode, and a non-aqueous electrolyte and transfer lithium ions or the like between the positive electrode and the negative electrode to charge and discharge have been widely used as high-output, high-capacity secondary batteries. Since secondary batteries are repeatedly charged and discharged, there is a demand for improved charge-discharge cycle characteristics.
[0003] For example, Patent Document 1 discloses a lithium ion secondary battery in which the charge / discharge cycle characteristics are improved by including in the positive electrode two types of positive electrode active material with different particle sizes that contain Co. Patent Document 2 discloses a lithium ion secondary battery in which the charge / discharge cycle characteristics are improved by including an electrolyte containing a lithium imide compound and a positive electrode that contains a positive electrode active material that contains Co. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2017-188466 A [Patent Document 2] JP 2008-210767 A Summary of the Invention
[0005] Patent Document 1 and Patent Document 2 disclose positive electrode active materials containing Co, and it is conceivable to design the lithium transition metal composite oxide contained in the positive electrode active material to have a high Ni content in order to obtain a high battery capacity, while decreasing the Co content in order to reduce the manufacturing cost. However, in a high Ni content lithium transition metal composite oxide that does not substantially contain Co, when the positive electrode is compressed to increase the density of the positive electrode active material, cracks may occur in the positive electrode active material, resulting in poor charge / discharge cycle characteristics and high battery resistance.
[0006] A non-aqueous electrolyte secondary battery according to an embodiment of the present disclosure includes a positive electrode, a negative electrode, and a non-aqueous electrolyte. The positive electrode has a positive electrode current collector and a positive electrode composite layer formed on the surface of the positive electrode current collector. The positive electrode active material contained in the positive electrode composite layer includes a lithium transition metal composite oxide that contains 85 mol % or more of Ni and 1 mol % to 15 mol % of Al relative to the total number of moles of metal elements excluding Li, and the total content of Ni, Al, and Mn is 99.9 mol % or more. The density of the positive electrode active material in the positive electrode composite layer is 3.45 g / cm. 3 The positive electrode is characterized in that, when a cross section of the positive electrode is observed with a scanning electron microscope, the ratio of the cross-sectional area of the lithium transition metal composite oxide without cracks to the cross-sectional area of the lithium transition metal composite oxide exposed on the cross section is 51% or more.
[0007] ADVANTAGEOUS EFFECTS OF THE DISCLOSURE According to the positive electrode active material for a nonaqueous electrolyte secondary battery according to one embodiment of the present disclosure, it is possible to reduce the battery resistance while suppressing the decrease in battery capacity that accompanies charging and discharging of the secondary battery. [Brief description of the drawings]
[0008] [Figure 1] FIG. 1 is a longitudinal sectional view of a nonaqueous electrolyte secondary battery according to an embodiment of the present invention. [Diagram 2] FIG. 2 is a schematic diagram illustrating the vicinity of the interface between a positive electrode current collector and a positive electrode mixture layer in a cross section of a positive electrode in one example of the embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] The lithium transition metal composite oxide contained as a positive electrode active material in the positive electrode of a secondary battery may crack when the positive electrode is compressed to increase the density of the positive electrode active material. When a crack occurs in the lithium transition metal composite oxide, a conductive path is not obtained inside the lithium transition metal composite oxide, and a portion that cannot contribute to charging and discharging is generated, and the battery capacity may decrease. In addition, when a crack occurs in the lithium transition metal composite oxide, the area in contact with the conductive material decreases, and the battery resistance may increase. Even in this case, if the lithium transition metal composite oxide is a lithium transition metal composite oxide containing Co, Co has high electronic conductivity, so that the effect of the resistance increase due to the crack can be reduced. However, when the Ni content is increased to obtain a high battery capacity, while the Co content is decreased to reduce the manufacturing cost, it is necessary to suppress the deterioration of the charge and discharge cycle characteristics and the increase in the battery resistance. As a result of intensive research into such a problem, the present inventors have found that in a high Ni-containing positive electrode active material that does not contain Co, the deterioration of the charge and discharge cycle characteristics and the increase in the battery resistance can be suppressed by adjusting the composition to a specific composition to increase the particle strength of the positive electrode active material.
[0010] An example of an embodiment of a nonaqueous electrolyte secondary battery according to the present disclosure will be described in detail below. A cylindrical battery in which a wound electrode body is housed in a cylindrical battery case will be exemplified below, but the electrode body is not limited to the wound type, and may be a laminate type in which a plurality of positive electrodes and a plurality of negative electrodes are alternately laminated one by one with a separator interposed therebetween. In addition, the battery case is not limited to a cylindrical shape, and may be, for example, a square shape, a coin shape, or the like, or may be a battery case made of a laminate sheet including a metal layer and a resin layer.
[0011] Fig. 1 is a longitudinal cross-sectional view of a nonaqueous electrolyte secondary battery 10 according to an embodiment. As illustrated in Fig. 1, the nonaqueous electrolyte secondary battery 10 includes an electrode assembly 14, a nonaqueous electrolyte (not shown), and a battery case 15 that accommodates the electrode assembly 14 and the nonaqueous electrolyte. The electrode assembly 14 has a wound structure in which a positive electrode 11 and a negative electrode 12 are wound with a separator 13 interposed therebetween. The battery case 15 includes a cylindrical outer can 16 with a bottom, and a sealing body 17 that closes the opening of the outer can 16.
[0012] The electrode body 14 is composed of a long positive electrode 11, a long negative electrode 12, two long separators 13, a positive electrode tab 20 joined to the positive electrode 11, and a negative electrode tab 21 joined to the negative electrode 12. The negative electrode 12 is formed to have a size slightly larger than the positive electrode 11 in order to prevent lithium deposition. That is, the negative electrode 12 is formed to be longer in the longitudinal direction and width direction (short direction) than the positive electrode 11. The two separators 13 are formed to have a size at least slightly larger than the positive electrode 11, and are arranged to sandwich the positive electrode 11, for example.
[0013] The nonaqueous electrolyte secondary battery 10 includes insulating plates 18, 19 disposed above and below the electrode body 14. In the example shown in Fig. 1, a positive electrode tab 20 attached to the positive electrode 11 passes through a through hole in the insulating plate 18 and extends toward the sealing body 17, and a negative electrode tab 21 attached to the negative electrode 12 passes outside the insulating plate 19 and extends toward the bottom side of the outer can 16. The positive electrode tab 20 is connected to the lower surface of a bottom plate 23 of the sealing body 17 by welding or the like, and a cap 27 of the sealing body 17 electrically connected to the bottom plate 23 serves as a positive electrode terminal. The negative electrode tab 21 is connected to the inner bottom surface of the outer can 16 by welding or the like, and the outer can 16 serves as a negative electrode terminal.
[0014] The exterior can 16 is, for example, a cylindrical metal container with a bottom. A gasket 28 is provided between the exterior can 16 and the sealing body 17, and the internal space of the battery case 15 is sealed. The exterior can 16 has a grooved portion 22 that supports the sealing body 17 and is formed, for example, by pressing the side portion from the outside. The grooved portion 22 is preferably formed in an annular shape along the circumferential direction of the exterior can 16, and supports the sealing body 17 on its upper surface.
[0015] The sealing body 17 has a structure in which a bottom plate 23, a lower valve body 24, an insulating member 25, an upper valve body 26, and a cap 27 are laminated in this order from the electrode body 14 side. Each member constituting the sealing body 17 has, for example, a disk shape or a ring shape, and each member except the insulating member 25 is electrically connected to each other. The lower valve body 24 and the upper valve body 26 are connected to each other at their respective centers, and the insulating member 25 is interposed between their respective peripheral edges. When the internal pressure of the battery increases due to abnormal heat generation, the lower valve body 24 deforms and breaks so as to push the upper valve body 26 toward the cap 27, and the current path between the lower valve body 24 and the upper valve body 26 is interrupted. When the internal pressure further increases, the upper valve body 26 breaks, and gas is discharged from the opening of the cap 27.
[0016] The positive electrode 11, negative electrode 12, separator 13, and nonaqueous electrolyte that constitute the nonaqueous electrolyte secondary battery 10, and in particular the positive electrode active material contained in the positive electrode mixture layer 31 that constitutes the positive electrode 11, will be described in detail below.
[0017] [Positive electrode] The positive electrode 11 has a positive electrode current collector 30 and a positive electrode composite layer 31 formed on the surface of the positive electrode current collector 30. The positive electrode composite layer 31 may be formed on both surfaces of the positive electrode current collector 30. The material of the positive electrode current collector 30 may be, for example, a foil of a metal such as stainless steel, aluminum, an aluminum alloy, or titanium, or a film having such a metal disposed on the surface layer. The positive electrode current collector 30 may further include a protective layer containing inorganic particles and a binder.
[0018] The positive electrode mixture layer 31 includes a positive electrode active material, a conductive material, and a binder. The thickness of the positive electrode mixture layer 31 is, for example, 10 μm to 150 μm. The positive electrode mixture layer 31 can be formed by applying a positive electrode mixture slurry to the surface of the positive electrode current collector 30, drying and compressing it. The positive electrode mixture slurry includes, for example, a conductive material, a binder, a positive electrode active material, and a dispersion medium. The positive electrode mixture slurry may be prepared by preparing a conductive material paste including a conductive material, a binder, and a dispersion medium, and then mixing it with the positive electrode active material. The positive electrode mixture slurry and the conductive material paste may include a dispersion medium.
[0019] Examples of the conductive material contained in the positive electrode mixture layer 31 include carbon powders such as carbon black, acetylene black, ketjen black, graphite, and carbon nanotubes. These may be used alone or in combination of two or more. Examples of the binder contained in the positive electrode mixture layer 31 include fluorine-based polymers and rubber-based polymers. Examples of the fluorine-based polymers include polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVdF), or modified versions thereof, and examples of the rubber-based polymers include ethylene-propylene-isoprene copolymers and ethylene-propylene-butadiene copolymers. These may be used alone or in combination of two or more. The dispersion medium of the positive electrode mixture slurry is, for example, N-methyl-2-pyrrolidone (NMP).
[0020] The positive electrode active material contained in the positive electrode mixture layer 31 includes a lithium transition metal composite oxide containing 85 mol% or more of Ni and 1 mol% or more and 15 mol% or less of Al relative to the total number of moles of metal elements excluding Li, and the total content of Ni, Al, and Mn is 99.9 mol% or more. Since the Ni content is high, a high-capacity battery can be obtained. In addition, since the total content of Ni, Al, and Mn accounts for most of the total amount of 99.9 mol% or more, the lithium transition metal composite oxide may contain only 0.1 mol% or less of Co relative to the total number of moles of metal elements excluding Li, and may be substantially free of Co. Here, "substantially free of Co" means that the lithium transition metal composite oxide contains only 0.01 mol% or less of Co.
[0021] The density of the positive electrode active material in the positive electrode mixture layer 31 is 3.45 g / cm 3 The above is the end of the process. As described above, the positive electrode mixture layer 31 formed on the surface of the positive electrode current collector 30 is compressed by a rolling roller or the like to increase the energy density. Compressing the positive electrode mixture layer 31 may cause cracks to occur in the lithium transition metal composite oxide.
[0022] In the observation of the cross section of the positive electrode by a scanning electron microscope (SEM), the ratio of the cross-sectional area of the lithium transition metal composite oxide without cracks to the cross-sectional area of the lithium transition metal composite oxide exposed on the cross section (hereinafter, sometimes referred to as the area ratio of particles without cracks) is 51% or more. At this time, the magnification of the observation by SEM is 700 times, and the observation area is about 20,000 μm 2 Here, the crack refers to a crack having a length of 3 μm or more that is visible when observed with an SEM at the above magnification. With a lithium transition metal composite oxide having the above composition, it is possible to increase the amount of the lithium transition metal composite oxide without cracks. This makes it possible to reduce the battery resistance while suppressing the decrease in battery capacity accompanying the charging and discharging of the secondary battery.
[0023] Furthermore, by compressing the positive electrode mixture layer 31, the lithium transition metal composite oxide contained in the positive electrode mixture layer 31 may bite into the surface of the positive electrode current collector 30, and the surface of the positive electrode current collector 30 in contact with the positive electrode mixture layer 31 may have a concave shape. When the lithium transition metal composite oxide bites into the positive electrode current collector 30, the contact area between the lithium transition metal composite oxide and the positive electrode current collector 30 increases, and the battery resistance can be reduced. In SEM observation of the cross section of the positive electrode 11, the length of the surface of the positive electrode current collector 30 in contact with the positive electrode mixture layer 31 may be 1.32 times or more the straight line length of the corresponding portion. For example, in FIG. 2 showing the vicinity of the interface between the positive electrode current collector 30 and the positive electrode composite layer 31 in the cross section of the positive electrode 11, the length of the surface of the positive electrode current collector 30 in contact with the positive electrode composite layer 31 is the total length of the line ab, the curve bc, the line cd, the curve de, and the line ef, and the straight line length of the corresponding portion is the line AF indicated by the imaginary arrow. In the cross section, the length of the surface of the positive electrode current collector 30 in contact with the positive electrode composite layer 31 is longer than the straight line length of the corresponding portion due to the presence of a concave portion. FIG. 2 is a diagram showing a schematic cross section of the positive electrode 11, and the observation magnification by SEM is 700 times, and the measured length in the cross section may be about 200 μm.
[0024] The lithium transition metal composite oxide has a layered structure. Examples of the layered structure of the lithium transition metal composite oxide include a layered structure belonging to the space group R-3m, a layered structure belonging to the space group C2 / m, and the like. Among these, in terms of high capacity, stability of the crystal structure, etc., it is preferably a layered structure belonging to the space group R-3m.
[0025] The lithium transition metal composite oxide has the general formula Li a Ni x Al y Mn z M v Nb w O 2-b (where 0.9 < a < 1.1, x ≥ 0.85, 0.01 ≤ y ≤ 0.15, 0 ≤ z ≤ 0.14, 0 ≤ v ≤ 0.001, 0 ≤ w ≤ 0.005, 0 ≤ b < 0.05, x + y + z + v + w = 1, and M is at least one element selected from Co, Fe, Ti, Si, Zr, Mo, and Zn). The composite oxide can be used. Note that the positive electrode active material may contain a lithium transition metal composite oxide other than that represented by the above general formula, or other compounds, as long as the object of the present disclosure is not impaired. The molar fraction of the metal element contained in the whole particles of the lithium transition metal composite oxide is measured by inductively coupled plasma (ICP) emission spectrometry.
[0026] It is preferable that a indicating the ratio of Li in the lithium transition metal composite oxide satisfies 0.9 ≤ a < 1.1, and more preferably satisfies 0.97 ≤ a ≤ 1.03. When a is less than 0.9, the battery capacity may decrease compared to the case where a satisfies the above range. When a is 1.1 or more, more Li compound needs to be added compared to the case where a satisfies the above range, so it may not be economical from the viewpoint of production cost.
[0027] The ratio y of Al to the total moles of metal elements other than Li in the lithium transition metal composite oxide is preferably 0.01≦y≦0.15, and more preferably 0.01≦y≦0.07. Since Al does not change its oxidation number during charging and discharging, it is believed that the structure of the transition metal layer is stabilized by being contained in the transition metal layer. On the other hand, when y>0.15, Al impurities are generated and the battery capacity is reduced. For example, Al may be uniformly dispersed in the layered structure of the lithium transition metal composite oxide, or may be present in a part of the layered structure.
[0028] Mn is an optional component. The ratio z of Mn to the total number of moles of metal elements other than Li in the lithium transition metal composite oxide preferably satisfies 0≦z≦0.14, and more preferably satisfies 0≦z≦0.05.
[0029] It is preferable that y>z is satisfied, as this improves the charge-discharge cycle characteristics.
[0030] Nb and M (M is at least one element selected from Co, Fe, Ti, Si, Zr, Mo, and Zn) are optional components. w, which indicates the ratio of Nb to the total number of moles of metal elements other than Li in the lithium transition metal composite oxide, preferably satisfies 0≦w≦0.005, and more preferably satisfies 0.001≦w≦0.005. By containing Nb within this range, the charge / discharge efficiency of the battery is improved. In addition, v, which indicates the ratio of M to the total number of moles of metal elements other than Li in the lithium transition metal composite oxide, preferably satisfies 0≦v≦0.001.
[0031] The lithium transition metal composite oxide is, for example, a secondary particle formed by agglomeration of a plurality of primary particles. The particle size of the primary particles constituting the secondary particles is, for example, 0.02 μm to 2 μm. The particle size of the primary particles is measured as the diameter of the circumscribed circle in a particle image observed by SEM.
[0032] The lithium transition metal composite oxide is a particle having a volume-based median diameter (D50) of, for example, 2 μm to 30 μm, preferably 2 μm to 20 μm, and more preferably 6 μm to 15 μm. D50 means a particle diameter at which the cumulative frequency is 50% from the smallest particle diameter in the volume-based particle size distribution, and is also called the median diameter. The particle size distribution of the lithium transition metal composite oxide can be measured using a laser diffraction type particle size distribution measuring device (e.g., MT3000II manufactured by Microtrack Bell Co., Ltd.) with water as a dispersion medium.
[0033] The content of the lithium transition metal composite oxide in the positive electrode active material is preferably 90 mass% or more, and more preferably 99 mass% or more, relative to the total mass of the positive electrode active material, from the standpoint of, for example, improving the battery capacity and effectively suppressing deterioration of the charge / discharge cycle characteristics.
[0034] The positive electrode active material of the present embodiment may contain other lithium transition metal composite oxides in addition to the lithium transition metal composite oxide of the present embodiment, such as lithium transition metal composite oxides having a Ni content of 0 mol % or more and less than 85 mol %.
[0035] Next, an example of a method for producing a lithium transition metal composite oxide will be described.
[0036] The method for producing a positive electrode active material includes, for example, a first step of obtaining a composite oxide containing Ni, Al, and an arbitrary metal element, a second step of mixing the composite oxide obtained in the first step with a lithium compound to obtain a mixture, and a third step of firing the mixture.
[0037] In the first step, for example, while stirring a solution of a metal salt containing Ni, Al, and an arbitrary metal element (Mn, Fe, etc.), an alkaline solution such as sodium hydroxide is dropped to adjust the pH to the alkaline side (e.g., 8.5 to 12.5), thereby precipitating (co-precipitating) a composite hydroxide containing Ni, Al, and the arbitrary metal element, and the composite hydroxide is calcined to obtain a composite oxide containing Ni, Al, and the arbitrary metal element. The calcination temperature is not particularly limited, but is, for example, in the range of 300°C to 600°C.
[0038] In the second step, the composite oxide obtained in the first step is mixed with a lithium compound to obtain a mixture. The lithium compound is, for example, Li 2 CO 3 , LiOH, Li 2 O 2 , Li 2 O, LiNO 3 , LiNO 2 , Li 2 SO 4 , LiOH H 2 O, LiH, LiF, etc. In addition, a niobium compound may be further mixed. The niobium compound is Nb 2 O 5 , Nb 2 O 5 nH 2 O, LiNbO 3 , NbCl 5 The mixing ratio of the above-mentioned composite oxide, Li compound, and Nb compound may be appropriately determined so that the respective elements in the Li transition metal oxide finally obtained have a desired ratio. The molar ratio of Li to the metal elements other than Li is, for example, 0.9 mol% or more and 1.1 mol% or less, and preferably 0.95 mol% or more and 1.05 mol% or less. When Nb is added, the molar ratio of Nb to the metal elements other than Li is, for example, 0.005 mol% or less, and preferably 0.001 mol% or more and 0.005 mol% or less. In the second step, when the composite oxide obtained in the first step and the lithium compound are mixed, other metal raw materials may be added as necessary. The other metal raw materials are oxides containing metal elements other than the metal elements constituting the composite oxide obtained in the first step, etc.
[0039] In the third step, the mixture obtained in the second step is fired under an oxygen atmosphere to obtain the lithium transition metal composite oxide according to this embodiment. In the third step, the heating rate from 450°C to 680°C is in the range of more than 1.0°C / min to 5.5°C / min, and the maximum temperature is in the range of 700°C to 850°C. The heating rate from over 680°C to the maximum temperature is, for example, 0.1 to 3.5°C / min. The holding time of the maximum temperature is 1 hour to 10 hours. The third step may be a multi-stage firing, and the first heating rate and the second heating rate may be set in a plurality of steps for each temperature range as long as they are within the above-specified range.
[0040] In the manufacturing method of this embodiment, in order to improve the battery capacity and safety, the lithium metal composite oxide powder may be washed with water after the third step. This washing with water may be performed by a known method and under known conditions, as long as lithium is not eluted from the lithium metal composite oxide and the battery characteristics are not deteriorated. In addition, a tungsten compound may be mixed before or after this washing with water. The tungsten compound is, for example, tungsten oxide, lithium tungstate, ammonium tungstate, etc. When mixed after washing with water, either a method of mixing after drying or mixing without drying by only solid-liquid separation may be used.
[0041] [Negative electrode] The negative electrode 12 has a negative electrode current collector 40 and a negative electrode composite layer 41 formed on the surface of the negative electrode current collector 40. The negative electrode composite layer 41 may be formed on both surfaces of the negative electrode current collector 40. As the negative electrode current collector 40, a non-porous conductive substrate (metal foil, etc.) or a porous conductive substrate (mesh, net, punched sheet, etc.) is used. Also, a film having a metal disposed on the surface layer can be used. Examples of the material of the negative electrode current collector include stainless steel, nickel, nickel alloy, copper, copper alloy, etc. The thickness of the negative electrode current collector is not particularly limited, but may be, for example, 1 to 50 μm, and may be 5 to 20 μm.
[0042] The negative electrode mixture layer 41 includes a negative electrode active material, a conductive material, a thickener, and a binder. The thickness of the negative electrode mixture layer 41 is, for example, 10 μm to 150 μm on one side of the negative electrode current collector 40. The negative electrode mixture layer 41 can be formed by applying a negative electrode mixture slurry to the surface of the negative electrode current collector 40 and drying it. The coating film after drying may be rolled as necessary. The negative electrode mixture slurry includes, for example, a conductive material, a binder, a thickener, a negative electrode active material, and a dispersion medium. A first negative electrode slurry may be applied to the surface of the negative electrode current collector 40, a second negative electrode slurry may be applied on the coating film of the first negative electrode slurry, and the coating films of the first negative electrode slurry and the second negative electrode slurry may be dried.
[0043] The negative electrode active material is not particularly limited as long as it is a material capable of absorbing and releasing lithium ions, and examples thereof include carbon materials, metals capable of forming an alloy with lithium or alloy compounds containing the metals. A mixture of a carbon material and an alloy compound can also be used. In addition to the above, a material having a higher charge / discharge potential with respect to metallic lithium, such as lithium titanate, than the carbon material can also be used. The ratio of the mass of the carbon material contained in the negative electrode active material layer to the mass of the alloy compound contained in the negative electrode active material layer may be, for example, 1 to 99, and may be 4 to 99.
[0044] As the carbon material, graphites such as natural graphite, non-graphitizable carbon, and artificial graphite, cokes, etc. can be used. As the carbon material, one type may be used alone, or two or more types may be used in combination. When graphite particles are used as the carbon material, a graphite-based material that has been conventionally used as a negative electrode active material for non-aqueous electrolyte secondary batteries may be used, and for example, natural graphite such as lump graphite and amorphous graphite, and artificial graphite such as lump artificial graphite and graphitized mesophase carbon microbeads can be used. The BET specific surface area of the graphite particles is 0.1 m 2 / g or more, 2 / g or more.
[0045] The alloy compound includes at least one metal capable of forming an alloy with lithium. As an element capable of forming an alloy with lithium, a silicon-containing material using silicon or a tin-containing material using tin can be used. These can also be combined with oxygen to form silicon oxide or tin oxide. The alloy compound may be in a particulate form, or directly bonded to the current collector. If it is in a particulate form, the particle size may be about 1 μm to 20 μm.
[0046] The silicon-containing material may be, for example, a lithium ion conductive phase or silicon composite particles in which silicon particles are dispersed in the lithium ion conductive phase. The lithium ion conductive phase may be, for example, a silicon oxide phase, a silicate phase, and / or a carbon phase. The main component of the silicon oxide phase (for example, 95% by mass to 100% by mass) may be silicon dioxide.
[0047] The silicate phase may contain at least one element selected from the group consisting of Group 1 elements and Group 2 elements of the long periodic table. Examples of Group 1 elements of the long periodic table and Group 2 elements of the long periodic table include lithium (Li), potassium (K), sodium (Na), magnesium (Mg), calcium (Ca), strontium (Sr), and barium (Ba). Other elements may include aluminum (Al), boron (B), lanthanum (La), phosphorus (P), zirconium (Zr), titanium (Ti), iron (Fe), chromium (Cr), and nickel (Ni). Among these, a silicate phase containing lithium (hereinafter sometimes referred to as a lithium silicate phase) is preferred because of its small irreversible capacity and high initial charge / discharge efficiency.
[0048] The lithium silicate phase may be an oxide phase containing lithium (Li), silicon (Si), and oxygen (O), and may contain other elements. The atomic ratio of O to Si in the lithium silicate phase: O / Si is, for example, greater than 2 and less than 4. Preferably, O / Si is greater than 2 and less than 3. The atomic ratio of Li to Si in the lithium silicate phase: Li / Si is, for example, greater than 0 and less than 4. The lithium silicate phase has the formula: Li 2z SiO 2+z (where 0 < z < 2). z preferably satisfies the relationship 0 < z < 1, and more preferably z = 1 / 2. Examples of elements other than Li, Si, and O that may be contained in the lithium silicate phase include iron (Fe), chromium (Cr), nickel (Ni), manganese (Mn), copper (Cu), molybdenum (Mo), zinc (Zn), aluminum (Al), zirconium (Zr), and the like.
[0049] The negative electrode 12 preferably contains silicon dioxide and an oxide phase containing at least Li, Si, and O.
[0050] The carbon phase can be composed of, for example, low-crystalline amorphous carbon (i.e., amorphous carbon). The amorphous carbon may be, for example, hard carbon, soft carbon, or others.
[0051] Examples of the conductive material contained in the negative electrode composite material layer 41 include carbon black such as acetylene black, carbon nanotubes, metal fibers, carbon fluoride, metal powders, conductive whiskers such as zinc oxide and potassium titanate, conductive metal oxides such as titanium oxide and graphene, and organic conductive materials such as phenylene derivatives. These may be used alone or in combination of two or more.
[0052] Examples of the thickener contained in the negative electrode mixture layer 41 include cellulose derivatives (such as cellulose ethers) such as carboxymethyl cellulose (CMC) and its modified products (including salts such as Na salts), methyl cellulose, etc., saponified polymers having vinyl acetate units such as polyvinyl alcohol, polyethers (polyalkylene oxides such as polyethylene oxide, etc.), etc. These may be used alone or in combination of two or more.
[0053] Examples of the binder contained in the negative electrode mixture layer 41 include resin materials, such as fluororesins such as polytetrafluoroethylene and polyvinylidene fluoride (PVDF); polyolefin resins such as polyethylene and polypropylene; polyamide resins such as aramid resin; polyimide and polyamideimide; acrylic resins such as polyacrylic acid, polymethyl acrylate, and ethylene-acrylic acid copolymer; vinyl resins such as polyacrylonitrile and polyvinyl acetate; polyvinylpyrrolidone; polyethersulfone; and rubber-like materials such as styrene-butadiene copolymer rubber (SBR). These may be used alone or in combination of two or more. As the polyacrylate, Li salt or Na salt is preferably used. Among them, it is preferable to use crosslinked lithium polyacrylate.
[0054] [Separator] For example, a porous sheet having ion permeability and insulating properties is used for the separator 13. Specific examples of the porous sheet include a microporous thin film, a woven fabric, and a nonwoven fabric. Suitable materials for the separator include olefin resins such as polyethylene (PE) and polypropylene (PP), and cellulose. The separator may be a laminate having a cellulose fiber layer and a thermoplastic resin fiber layer such as an olefin resin. The laminate may be a laminate of a polyolefin resin and a cellulose fiber layer, or a two-layer structure of PE / PP or a three-layer structure of PE / PP / PE in which different polyolefin resins are laminated.
[0055] [Non-aqueous electrolyte] The non-aqueous electrolyte includes a non-aqueous solvent and an electrolyte salt dissolved in the non-aqueous solvent. The non-aqueous electrolyte may be liquid or gel. The liquid non-aqueous electrolyte (non-aqueous electrolyte solution) is prepared by dissolving an electrolyte salt in a non-aqueous solvent. The gel non-aqueous electrolyte may be a solid electrolyte including a non-aqueous electrolyte solution and a matrix polymer. As the matrix polymer, for example, a polymer material that absorbs a solvent and gels is used. Such polymer materials include fluororesin, acrylic resin, and / or polyether resin.
[0056] The non-aqueous solvent may be, for example, esters, ethers, nitriles, amides such as dimethylformamide, or a mixture of two or more of these. The non-aqueous solvent may contain a halogen-substituted product in which at least a part of the hydrogen of the solvent is substituted with a halogen atom such as fluorine. The non-aqueous solvent may be used alone or in combination of two or more. The amount of the non-aqueous solvent in the non-aqueous electrolyte is, for example, 5 to 100% by mass.
[0057] Examples of the esters include cyclic carbonates (excluding unsaturated cyclic carbonates described below), chain carbonates, cyclic carboxylates, and chain carboxylates. Examples of cyclic carbonates include propylene carbonate (PC), ethylene carbonate (EC), and butylene carbonate. Examples of chain carbonates include diethyl carbonate (DEC), ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), methyl propyl carbonate, ethyl propyl carbonate, and methyl isopropyl carbonate. Examples of cyclic carboxylates include γ-butyrolactone (GBL), γ-valerolactone (GVL), and the like. Examples of chain carboxylates include methyl formate, ethyl formate, propyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, and methyl pivalate.
[0058] Examples of the ethers include cyclic ethers, chain ethers, etc. Examples of cyclic ethers include 1,3-dioxolane, 4-methyl-1,3-dioxolane, tetrahydrofuran, 2-methyltetrahydrofuran, propylene oxide, 1,2-butylene oxide, 1,3-dioxane, 1,4-dioxane, 1,3,5-trioxane, furan, 2-methylfuran, 1,8-cineole, and crown ether. Examples of chain ethers include 1,2-dimethoxyethane, diethyl ether, dipropyl ether, diisopropyl ether, dibutyl ether, dihexyl ether, ethyl vinyl ether, butyl vinyl ether, methyl phenyl ether, ethyl phenyl ether, butyl phenyl ether, pentyl phenyl ether, methoxytoluene, benzyl ethyl ether, diphenyl ether, dibenzyl ether, o-dimethoxybenzene, 1,2-diethoxyethane, 1,2-dibutoxyethane, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, diethylene glycol dibutyl ether, 1,1-dimethoxymethane, 1,1-diethoxyethane, triethylene glycol dimethyl ether, and tetraethylene glycol dimethyl ether.
[0059] Examples of the nitriles include acetonitrile, propionitrile, butylnitrile, valeronitrile, n-heptanenitrile, succinonitrile, glutaronitrile, adiponitrile, pimelonitrile, 1,2,3-propanetricarbonyl, and 1,3,5-pentanetricarbonitrile.
[0060] Examples of the halogen-substituted compounds include fluorinated ethers, fluorinated cyclic carbonates, fluorinated chain carbonates, and fluorinated chain carboxylates such as methyl fluoropropionate (FMP). Examples of fluorinated ethers include 2,2,2-trifluoroethyl methyl ether and 1,1,2,2-tetrafluoroethyl-2,2,2-trifluoroethyl. Examples of fluorinated cyclic carbonates include 4-fluoroethylene carbonate (FEC), 4,5-difluoroethylene carbonate, 4,4-difluoroethylene carbonate, 4,4,5-trifluoroethylene carbonate, and 4,4,5,5-tetrafluoroethylene carbonate. Examples of fluorinated chain carboxylates include fluorinated ethyl propionate, fluorinated methyl acetate, fluorinated ethyl acetate, fluorinated propyl acetate, 2,2,2-ethyl trifluoroacetate, 3,3,3-methyl trifluoropropionate, and methyl pentafluoropropionate.
[0061] The electrolyte salt may be a lithium salt, etc. The concentration of the lithium salt in the non-aqueous electrolyte is, for example, 0.5 to 3 mol / L, and preferably 0.8 to 1.5 mol / L.
[0062] The lithium salt is, for example, LiClO 4 , LiBF 4 , LiPF 6 , LiAlCl 4 , LiSbF 6 , LiSCN, LiCF 3 SO 3 , LiCF 3 CO 2 , LiAsF 6 , LiB 10 Cl 10 , lower aliphatic lithium carboxylate, LiCl, LiBr, LiILi(P(C 2 O 4 )F 4 ), LiPF 6-x (C n F 2n+1 ) x(1 < x < 6, n is 1 or 2), examples include chloroborane lithium, borates, phosphates, imide salts, etc. Examples of borates include Li[B(C 2 O 4 ) 2 , Li[B(C 2 O 4 )F 2 , Li 2 B 4 O 7 , lithium bis(1,2-benzenediolate(2-)-O,O’), lithium bis(2,3-naphthalenediolate(2-)-O,O’), lithium bis(2,2’-biphenyldiolate(2-)-O,O’), lithium bis(5-fluoro-2-olate-1-benzenesulfonate-O,O’), etc. Examples of phosphates include Li[P(C 2 O 4 )F 4 , Li[P(C 2 O 4 ) 2 F 2 , Li[P(C 2 O 4 ) 3 , etc. Examples of imide salts include lithium bis(fluorosulfonyl)imide (LiN(FSO 2 ) 2 : hereinafter also referred to as LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiN(CF 3 SO 2 ) 2 ), lithium trifluoromethanesulfonate nonafluorobutanesulfonate imide (LiN(CF 3 SO 2 )(C 4 F 9 SO 2 )), lithium bis(pentafluoroethanesulfonyl)imide (LiN(C 2 F 5 SO 2 ) 2 ), LiN(C l F 2l+1 SO 2 )(C m F 2m+1 SO 2) {l and m are integers of 0 or more}. The lithium salt may be used alone or in combination of two or more.
[0063] The electrolyte salt is, in particular, LiPF 6 It is preferable to use LiFSI in combination with LiPF. The concentration of LiFSI in the electrolyte is preferably 0.1 mol / L or more and 1.0 mol / L or less. 6 The concentration of LiFSI and LiPF in the electrolyte is preferably 0.5 mol / L or more and 1.5 mol / L or less. 6 The total concentration of LiFSI and LiPF is preferably 1 mol / L or more and 2 mol / L or less. 6 When used in combination with LiFSI and LiPF 6 The effects of these factors are well balanced, and the initial charge / discharge efficiency of the battery is further improved.
[0064] The electrolytic solution may contain additives. The amount of these additives in the non-aqueous electrolyte is, for example, 0.01 to 20% by mass. Examples of the additives include unsaturated carbonate esters, acid anhydrides, phenol compounds, benzene compounds, nitrile compounds, isocyanate compounds, sultone compounds, sulfuric acid compounds, borate ester compounds, phosphate ester compounds, and phosphite ester compounds.
[0065] Examples of the unsaturated cyclic carbonate include vinylene carbonate, 4-methylvinylene carbonate, 4,5-dimethylvinylene carbonate, 4-ethylvinylene carbonate, 4,5-diethylvinylene carbonate, 4-propylvinylene carbonate, 4,5-dipropylvinylene carbonate, 4-phenylvinylene carbonate, 4,5-diphenylvinylene carbonate, vinylethylene carbonate, and divinylethylene carbonate. The unsaturated cyclic carbonate may be used alone or in combination of two or more. The unsaturated cyclic carbonate may have a part of hydrogen atoms substituted with fluorine atoms.
[0066] The acid anhydride may be an anhydride in which a plurality of carboxylic acid molecules are condensed together, but is preferably an acid anhydride of a polycarboxylic acid, such as succinic anhydride, maleic anhydride, or phthalic anhydride.
[0067] Examples of the phenol compound include phenol and hydroxytoluene.
[0068] Examples of benzene compounds include fluorobenzene, hexafluorobenzene, and cyclohexylbenzene (CHB).
[0069] Examples of the nitrile compound include adiponitrile, pimelonitrile, propionitrile, and succinonitrile.
[0070] Examples of the isocyanate compound include methyl isocyanate (MIC), diphenylmethane diisocyanate (MDI), hexamethylene diisocyanate (HDI), toluene diisocyanate (TDI), isophorone diisocyanate (IPDI), and bisisocyanate methylcyclohexane (BIMCH).
[0071] Examples of the sultone compound include propane sultone and propene sultone.
[0072] Examples of the sulfate compound include ethylene sulfate, ethylene sulfite, dimethyl sulfate, and lithium fluorosulfate.
[0073] Examples of the borate ester compound include trimethylborate and tris(trimethylsilyl)borate.
[0074] Examples of the phosphate ester compound include trimethyl phosphate and tris(trimethylsilyl) phosphate.
[0075] Examples of the phosphite ester compound include trimethyl phosphite and tris(trimethylsilyl) phosphite.
[0076] The non-aqueous electrolyte contains a non-aqueous solvent, an electrolyte salt, and an additive, and the additive preferably contains 1 mass % to 5 mass % of vinylene carbonate and 5 mass % to 15 mass % of fluoroethylene carbonate relative to the total mass of the non-aqueous solvent and the electrolyte salt.
[0077] <Example> The present disclosure will be further described below with reference to examples and comparative examples, but the present disclosure is not limited to the following examples.
[0078] [Preparation of positive electrode active material] <Example 1> [Ni 0.92 Al 0.05 Mn 0.03 ](OH) 2 The composite hydroxide represented by the formula (I) was calcined at 500°C for 8 hours to obtain the composite oxide (Ni 0.92 Al 0.05 Mn 0.03 O 2 ) was obtained. LiOH and the above composite oxide were mixed so that the molar ratio of Li to the total amount of Ni, Al, and Mn was 1.03:1 to obtain a mixture. The mixture was heated from room temperature to 650°C at a heating rate of 2.0°C / min in an oxygen stream, and then fired from 650°C to 730°C at a heating rate of 0.5°C / min to obtain a fired product. The fired product was washed with water, and after solid-liquid separation, tungsten oxide was mixed therewith so that the amount was 0.01 mol% relative to the total molar amount of Ni, Al, and Mn in the fired product, and then dried to obtain a lithium transition metal compound. The composition of the obtained positive electrode active material was measured using an ICP emission spectrometer (manufactured by Thermo Fisher Scientific, product name "iCAP6300"), and the composition was found to be LiNi 0.92 Al 0.05 Mn 0.03 O 2 This was used as the positive electrode active material of Example 1.
[0079] <Example 2> [Ni 0.91 Al 0.06 Mn 0.03 ](OH) 2 Using the composite hydroxide represented by 0.91 Al 0.06 Mn 0.03 O 2 A positive electrode active material was obtained in the same manner as in Example 1, except that LiOH and the above composite oxide were mixed so that the molar ratio of Li to the total amount of Ni, Al, and Mn was 1.03:1 to obtain a mixture. The composition of the obtained positive electrode active material was LiNi 0.91 Al 0.06 Mn 0.03 O 2 This was used as the positive electrode active material of Example 2.
[0080] <Example 3> [Ni 0.92 Al 0.05 Mn 0.03 ](OH) 2 Using the composite hydroxide represented by 0.92 Al 0.05 Mn 0.03 O 2 ) was obtained, and LiOH, the above composite oxide, and Nb 2 O 5 A positive electrode active material was obtained in the same manner as in Example 1, except that the above was mixed so that the molar ratio of Li, the total amount of Ni, Al, and Mn, and Nb was 1.03:1:0.002. 0.92 Al 0.05 Mn 0.03 Nb 0.002 O 2 This was used as the positive electrode active material of Example 3.
[0081] <Example 4> [Ni 0.91 Al 0.06 Mn 0.03 ](OH) 2 Using the composite hydroxide represented by 0.91 Al 0.06 Mn 0.03 O 2) was obtained, and LiOH, the above composite oxide, and Nb 2 O 5 A positive electrode active material was obtained in the same manner as in Example 1, except that the above was mixed so that the molar ratio of Li, the total amount of Ni, Al, and Mn, and Nb was 1.03:1:0.002. 0.91 Al 0.06 Mn 0.03 Nb 0.002 O 2 This was used as the positive electrode active material of Example 4.
[0082] <Example 5> [Ni 0.94 Al 0.06 ](OH) 2 Using the composite hydroxide represented by 0.94 Al 0.06 O 2 A positive electrode active material was obtained in the same manner as in Example 1, except that LiOH and the above composite oxide were mixed so that the molar ratio of Li to the total amount of Ni and Al was 1.03:1 to obtain a mixture. The composition of the obtained positive electrode active material was LiNi 0.94 Al 0.06 O 2 This was used as the positive electrode active material of Example 5.
[0083] <Comparative Example> [Ni 0.80 Mn 0.20 ](OH) 2 Using the composite hydroxide represented by 0.80 Mn 0.20 O 2 A positive electrode active material was obtained in the same manner as in Example 1, except that LiOH and the above composite oxide were mixed so that the molar ratio of Li to the total amount of Ni and Mn was 1.03:1 to obtain a mixture. The composition of the obtained positive electrode active material was LiNi 0.80 Mn 0.20 O 2 This was used as the positive electrode active material of the comparative example.
[0084] <Reference example> [Ni 0.91 Co 0.05 Al0.04 ](OH) 2 Using the composite hydroxide represented by 0.91 Co 0.05 Al 0.04 O 2 A positive electrode active material was obtained in the same manner as in Example 1, except that LiOH and the above composite oxide were mixed so that the molar ratio of Li to the total amount of Ni, Co, and Al was 1.03:1 to obtain a mixture. The composition of the obtained positive electrode active material was LiNi 0.91 Co 0.05 Al 0.04 O 2 This was used as the positive electrode active material of the reference example.
[0085] Next, test cells were fabricated as follows using the positive electrode active materials of Examples 1 to 5, Comparative Example, and Reference Example.
[0086] [Preparation of positive electrode] A positive electrode mixture slurry was prepared by mixing 91 parts by mass of the positive electrode active material of Examples 1 to 5, Comparative Example, and Reference Example, 7 parts by mass of acetylene black as a conductive material, and 2 parts by mass of polyvinylidene fluoride as a binder, and mixing this with N-methyl-2-pyrrolidone (NMP). Next, the slurry was applied to a positive electrode current collector made of aluminum foil with a thickness of 15 μm, and after drying the coating film, the coating film was rolled with a rolling roller and cut into a predetermined electrode size to obtain a positive electrode in which a positive electrode mixture layer was formed on both sides of the positive electrode current collector. In addition, an exposed portion was provided in which the surface of the positive electrode current collector was exposed in a part of the positive electrode. Positive electrodes were prepared in the same manner in Examples 2 to 5, Comparative Example, and Reference Example. In all positive electrodes, the density of the positive electrode active material in the positive electrode mixture layer was 3.6 g / cm 3 It was.
[0087] [Preparation of negative electrode] Natural graphite was used as the negative electrode active material. The negative electrode active material, sodium carboxymethylcellulose (CMC-Na), and styrene-butadiene rubber (SBR) were mixed in an aqueous solution at a solid content mass ratio of 100:1:1 to prepare a negative electrode composite slurry. The negative electrode composite slurry was applied to both sides of a negative electrode current collector made of copper foil, and the coating film was dried. The coating film was then rolled using a rolling roller and cut to a predetermined electrode size to obtain a negative electrode in which a negative electrode composite layer was formed on both sides of the negative electrode current collector. An exposed portion was provided in part of the negative electrode, where the surface of the negative electrode current collector was exposed.
[0088] [Preparation of non-aqueous electrolyte] Ethylene carbonate (EC), methyl ethyl carbonate (MEC), and dimethyl carbonate (DMC) were mixed in a volume ratio of 3:3:4. Lithium hexafluorophosphate (LiPF 6 ) was dissolved in water to a concentration of 1.2 mol / L to prepare a non-aqueous electrolyte.
[0089] [Preparation of test cell] An aluminum lead was attached to the exposed part of the positive electrode containing the positive electrode active material of Examples 1 to 5, Comparative Example, and Reference Example, and a nickel lead was attached to the exposed part of the negative electrode, and the positive electrode and the negative electrode were spirally wound with a polyolefin separator interposed therebetween, and then pressed in the radial direction to prepare a flat wound electrode body. This electrode body was placed in an exterior body, and the nonaqueous electrolyte was injected, and the opening of the exterior body was sealed to obtain a test cell.
[0090] For each test cell, the capacity retention rate before and after the cycle test and the DC resistance of the battery were evaluated. The results are shown in Table 1. Table 1 also shows the composition of the positive electrode active material of Examples 1 to 5, Comparative Example, and Reference Example, the area ratio of crack-free particles, and the ratio of the length of the surface of the positive electrode current collector in contact with the positive electrode mixture layer to the straight line length of the corresponding part (hereinafter, sometimes referred to as the ratio of the positive electrode current collector surface length to the straight line).
[0091] [Evaluation of capacity retention rate] The following cycle test was carried out on the batteries prepared by incorporating the positive electrodes containing the positive electrode active materials of Examples 1 to 5, Comparative Example, and Reference Example. The discharge capacity at the first cycle and the discharge capacity at the 100th cycle of the cycle test were obtained, and the capacity retention rate was calculated by the following formula.
[0092] Capacity retention rate (%) = (100th cycle discharge capacity ÷ 1st cycle discharge capacity) × 100 <Cycle test> The test cell was charged at a constant current of 0.3 It in a temperature environment of 25°C until the battery voltage reached 4.2 V, and then charged at a constant voltage of 0.02 It at 4.2 V. It was then discharged at a constant current of 0.5 It until the battery voltage reached 2.5 V. This charge / discharge cycle was repeated 100 times.
[0093] [Evaluation of DC resistance] In an environment of 25°C, the battery was charged at a constant current of 0.3 It until the battery voltage reached 4.2 V, and then was charged at a constant voltage of 0.02 It at 4.2 V. After that, the battery was stored for 1 hour in an environment of 25°C, and then was discharged at a constant current of 0.5 It until the battery voltage reached 2.5 V. The DC resistance was calculated by dividing the difference between the open circuit voltage (OCV) and the closed circuit voltage (CCV) 10 seconds after discharge by the discharge current 10 seconds after discharge, as shown in the following formula.
[0094] DC resistance = [OCV-CCV (after 10 seconds of discharge)] / discharge current (after 10 seconds of discharge)
[0095] [Table 1]
[0096] In Examples 1 to 5, the capacity retention rate was higher and the DC resistance was smaller than in the comparative example. Furthermore, in Examples 1 to 5, the capacity retention rate and the DC resistance were approximately the same as in the reference example containing Co. From this result, it was found that by using a positive electrode active material in which the occurrence of cracks is suppressed by adjusting the composition, it is possible to suppress the decrease in battery capacity accompanying charge and discharge to the same extent as a positive electrode active material containing Co, and to reduce the battery resistance. [Explanation of symbols]
[0097] 10 Nonaqueous electrolyte secondary battery 11 Positive electrode 12 Negative electrode 13 Separator 14 Electrode body 15 Battery case 16 Outer can 17 Sealing body 18,19 Insulating plate 20 Positive tab 21 Negative electrode tab 22 Grooved part 23 Bottom plate 24 Lower valve body 25 Insulating materials 26 Upper valve 27 Cap 28 Gasket 30 Positive electrode current collector 31 Positive electrode mixture layer 40 Negative electrode current collector 41 Negative electrode composite layer
Claims
1. A non-aqueous electrolyte secondary battery comprising a positive electrode, a negative electrode, and a non-aqueous electrolyte, The positive electrode has a positive electrode current collector and a positive electrode mixture layer formed on a surface of the positive electrode current collector, The positive electrode active material contained in the positive electrode mixture layer contains 85 mol % or more of Ni, 1 mol % or more and 15 mol % or less of Al, and 0.1 mol % or more and 0.5 mol % or less of Nb, relative to the total number of moles of metal elements excluding Li, and includes a lithium transition metal composite oxide in which the total content of Ni, Al, and Mn is 99.9 mol % or more; The density of the positive electrode active material in the positive electrode mixture layer is 3.45 g / cm 3 That's all. a ratio of a cross-sectional area of the lithium transition metal composite oxide without cracks to a cross-sectional area of the lithium transition metal composite oxide exposed on the cross-section, when the cross-section of the positive electrode is observed with a scanning electron microscope, is 51% or more.
2. The lithium transition metal composite oxide has the general formula Li a Ni x A y Mn z M v Nb w O 2-b 2. The nonaqueous electrolyte secondary battery according to claim 1, wherein: (wherein 0.9<a<1.1, x≧0.85, 0.01≦y≦0.15, 0≦z≦0.14, 0≦v≦0.001, 0≦w≦0.005, 0≦b<0.05, x+y+z+v+w=1, and M is at least one element selected from Co, Fe, Ti, Si, Zr, Mo, and Zn).
3. 3. The nonaqueous electrolyte secondary battery according to claim 2, wherein in the general formula representing the lithium transition metal composite oxide, 0.01≦y≦0.07 and 0≦z≦0.
05.
4. 4. The nonaqueous electrolyte secondary battery according to claim 2, wherein in the general formula representing the lithium transition metal composite oxide, y>z.
5. 5. The nonaqueous electrolyte secondary battery in accordance with claim 1, wherein the lithium transition metal composite oxide is substantially free of Co.
6. a surface of the positive electrode current collector in contact with the positive electrode mixture layer has a concave shape, 6. The nonaqueous electrolyte secondary battery according to claim 1, wherein, in observation of a cross section of the positive electrode with a scanning electron microscope, a length of a surface of the positive electrode current collector in contact with the positive electrode mixture layer is 1.32 times or more the linear length of a corresponding portion.
7. The non-aqueous electrolyte includes a non-aqueous solvent, an electrolyte salt, and an additive, The nonaqueous electrolyte secondary battery according to any one of claims 1 to 6, wherein the additive comprises 1 mass% to 5 mass% of vinylene carbonate and 5 mass% to 15 mass% of fluoroethylene carbonate, based on the total mass of the nonaqueous solvent and the electrolyte salt.
8. 8. The nonaqueous electrolyte secondary battery according to claim 1, wherein the negative electrode comprises silicon dioxide and an oxide phase containing at least Li, Si, and O.
Citation Information
Patent Citations
Non-aqueous electrolyte secondary cell
JP2001102091A
battery
JP2004356092A
Positive active material for nonaqueous electrolyte lithium ion secondary battery and its manufacturing method
JP2008124038A
Lithium secondary battery
JP2008210767A
Silicon graphite complex particle and method for manufacturing the same
JP2016091762A